SISTEM PAKAR MENDETEKSI PENENTUAN PENYAKIT ANEMIA MENGGUNAKAN METODE TEOREMA BAYES STUDI KASUS LABORATORIUM ANUGERAH RANTAUPRAPAT - Hasibuan, Abdul Khairul Arby Hasibuan; Watrianthos, Ronal; Pasaribu, Endi Zunaedy (U-NET Jurnal Teknik Informatika, 2024)
Expert systems are a branch of artificial intelligence that studies how to adopt an expert's way of thinking in solving a problem and making a decision to reach a conclusion. In this case, an expert system is used to diagnose anemia. What was discussed was how to determine the type of disease, how to overcome anemia in society and designing an expert system using technology. anemia is caused by a lack of red blood cells or red blood cells that do not function in the body. This causes reduced oxygen flow to the body's organs. Vitamin B supplements can be used for low vitamin levels. The Bayes method is a method for producing parameter estimates by combining information from samples and other previously available information. Bayes' theorem is used to calculate the probability of an event occurring based on the influence obtained from the results of the observation. From several studies that have been carried out, solutions have been obtained to prevent anemia. Anemia can cause weakness and headaches due to lack of blood, which can lead to complications.